Ações do Ministério Público Federal na rede sociotécnica constituída a partir da UHE do Baixo Iguaçu - Neves, Leomar Antonio das (2017)
This dissertation analyzes the actions of the Public Ministry in the socio-technical network constituted from the UHE of Baixo Iguaçu. The research sought more specifically, to map the network, as well as to identify the actions triggered by the Federal Public Ministry in the established network. In order to verify how the Federal Public Prosecutor's Office has positioned itself in the network, identifying the controversies existing in the network around this actant. In this sense, the work was based on the theoretical approach of actor network theory. The research comprised the analysis of empirical data from field research that utilized documentary research and semi-structured interviews made later with the actants who were identified and analyzed the controversies and found that the MPF acted as mouthpiece of nonhumans occurring the process of Callon's translation (1986) and treachery in the network by MPF and human actants.